Street waste pickers: A case for Appropriate Technology, Social Entrepreneurship and Innovation - Vusumuzi Malele (Diponegoro University, 2022)
Street waste pickers, pushing their trolleys, are an everyday sight in many cities in South Africa. These paper reports on the pragmatic approach that was used to explore whether or not waste pickers/collectors need or already have the appropriate technology to conduct their daily activities. In this regard, street waste pickers in the northern part of Pretoria were interviewed to solicit information regarding the access to appropriate technologies and why they think there is a need for such technologies in their environment. The focus of the study was to assess the waste pickers environment as a potential innovation space for appropriate technology (AT). It was found that the environment provide a platform for the development of related AT research and development as well as social entrepreneurship and innovation.